A Conceptual Model of Helpfulness of Online Reviews in a Blink - BhÄle, Sanjay; Tongare, Ketan (Indian Journal of Marketing, 2018)
Online reviews have become the essence of information for consumers while making a purchase decision in online environments, though it is still critical to ascertain the quantum of influence it drives in making the purchase decision. Although the importance of online reviews has been examined, there are research gaps in studies on how to make online reviews helpful in a blink from the purchase intention point of view. This paper explored the aspects that influenced the formation of the title of online reviews. The study proposed a conceptual framework for the title of online reviews by adopting elements such as reviewers' identity, online recommendation, online review syndrome, age in online reviews, and law of closure and halo-effect that make each review helpful. The effect of the conceptual model could help enhance the formation of opinion of the consumers in a blink. The study integrated online review literature and presented a model of helpfulness for online reviews in a blink. Online companies should focus upon upgrading the online review system and enrich customer experience to maintain a positive relationship with their users.